Land without Dreams, 2018: Co-produced with Eventministeriet/The Royal Danish Theatre. - Exe Christoffersen, Erik (Peripeti, 2023)
Land without Dreams is produced by FIX&FOXY in collaboration with Eventministeriet at The Royal Danish Theatre. Actor: Lise Lauenblad. Director and writer: Tue Biering. Dramaturge: Tanja Diers.